Comparison of subtalar mobilization with conventional physiotherapy treatment for the management of planter fasciitis - Muhammad Kashif; Abdulaziz Aoudh Albalwi; Ahmed Abdullah Alharbi; Humaira Iram; Nosheen Manzoor (Journal of the Pakistan Medical Association, 2021)
Objective: To compare the effectiveness of subtalar mobilization with movement (Mulligan technique) with conventional physiotherapy treatment for the management of planter fasciitis. Material and Methods: A single blinded randomized trial was conducted at the Prime Care Hospital, Faisalabad, Pakistan from January 2017 to August 2017. Sixty Participants were divided into intervention and control groups through a computerized random numbers. Intervention group was treated with subtalar mobilization with movement (Mulligan technique), and control group was given conventional physiotherapy for three-weeks. SPSS 20 was used for data analysis. Results: The mean age of the participants in the intervention group was 32.40 ± 8.02 years and the control group 32.59 ± 7.00 years. The mean BMI in intervention and control groups was 25.35 and 25.67, respectively. The result of our study showed that there were significant differences (P-value <0.05) between the VAS values before and after the intervention in the 3rd week between the intervention and the control group. Moreover, the intervention group showed more reduction in disability (p=0.03) compared to the control group. Conclusion: Our study concluded both methods to demonstrate benefits. However, Subtalar mobilization with movement (Mulligan technique) plus rigid tapping reduced pain and disability more effectively than conventional physiotherapy plus rigid tapping in patients with planter fasciitis. All protocols for this clinical study were registered with WHO recognized Clinical Trial Registry, with the registration number RCT20200221046567N2. Key Words: Heel pain, plantar fasciitis, physiotherapy, mobilization, mulligan technique, taping.